2023
DOI: 10.1371/journal.pone.0294226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MEF2A and SLC22A3-LPAL2-LPA gene polymorphisms on warfarin sensitivity and responsiveness in Jordanian cardiovascular patients

Laith N. AL-Eitan,
Ayah Y. Almasri,
Adan H. Alnaamneh
et al.

Abstract: Aims This study aims to investigate the influence of MEF2A and SLC22A3-LPAL2-LPA polymorphisms on cardiovascular disease susceptibility and responsiveness to warfarin medication in Jordanian patients, during the initiation and maintenance phases of treatment. Backgrounds Several candidate genes have been reported to be involved in warfarin metabolism and studying such genes may help in finding an accurate way to determine the needed warfarin dose to lower the risk of adverse drug effects, resulting in more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In conclusion, our data imply that only the rs10739150 genotype of the PTPRD gene shows an increased risk of hypertension, and the G allele is strongly related to the disease development. Considering the paucity of studies concerning pharmacogenetics and personalized medicine in Jordan [ 52 54 ], larger sample sizes and family-based analyses are needed to understand the biochemical processes and mechanisms by which this genetic variation impacts hypertension susceptibility, as well as to assess the implications on drug responsiveness. Our study is the first of its kind that uses Jordanian Arab descendants, thus raising the question of the effect of genetic polymorphisms and ethnicity on hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our data imply that only the rs10739150 genotype of the PTPRD gene shows an increased risk of hypertension, and the G allele is strongly related to the disease development. Considering the paucity of studies concerning pharmacogenetics and personalized medicine in Jordan [ 52 54 ], larger sample sizes and family-based analyses are needed to understand the biochemical processes and mechanisms by which this genetic variation impacts hypertension susceptibility, as well as to assess the implications on drug responsiveness. Our study is the first of its kind that uses Jordanian Arab descendants, thus raising the question of the effect of genetic polymorphisms and ethnicity on hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous gene families have been implicated in cardiovascular diseases, with multiple genetic variations spread across the Jordanian population. Research has also indicated that several SNPs may also influence the response to cardiovascular medications such as warfarin [35][36][37][38][39][40][41][42][43][44]. However, the relationship between polymorphism within the ACE gene and HTN is still debatable and has so far been inconclusive; the reason is ethnic variations and geographic features.…”
Section: Introductionmentioning
confidence: 99%